The impact of empowering leadership on innovative work behaviour in Chinese universities: the role of work engagement - Zhang, Xueqi (2022)
Promoting high-quality development in education poses new challenges for innovation in Chinese universities. Innovative work behaviour plays an important role in driving innovation in organisations. Some scholars have previously conducted research on the factors that influence innovative work behaviour. Empowering leadership is an emerging leadership style and further research into it as an influencing factor has yet to be added. Empowering leadership and work engagement are noted to contribute to the development of innovative work behaviours. Furthermore, work engagement mediates the impact of empowering leadership on innovative work behaviour. Therefore, this research aims to investigate the mechanisms influencing the relationship between empowered leadership, work engagement and innovative work behaviour in the Chinese university context, in order to better guide Chinese universities in their innovation. As many previous studies have explored the relationship between empowered leadership and innovative work behaviour in the corporate context, few scholars have examined how empowered leadership influences innovative work behaviour in the Chinese university context. As such, this research seeks to explore the relationship between empowering leadership and innovative work behaviour within higher education organisations in a distinctive Chinese culture, and to investigate whether work engagement can form a mediating influence relationship between empowering leadership and innovative work, thereby providing direction to guide innovation in Chinese universities. This study uses quantitative research methods and SPSS to statistically analyse the data collected from the questionnaires distributed. A total of 608 teachers and teaching staff from within universities across China participated in this questionnaire survey research. The data were then combined with reliability analysis, descriptive statistical analysis and correlation analysis, and further mediating relationships were tested using stratified multiple regression analysis. The findings from the research suggest that in the Chinese university context, empowering leadership plays an important role in promoting innovative work behaviour. Moreover, work engagement plays an integral role in mediating the relationship between empowering leadership and innovative work behaviour.